Republic of Mozambique : Poverty Reduction Strategy Paper Progress Report (Review of the Economic and Social Plan for 2003). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper reviews Mozambique's economic and social plan for 2003. It presents the actions that have been taken to improve the current planning instrument. The paper outlines the social and demographic profile of Mozambique and reviews the extent to which the current strategy for the reduction of absolute poverty in the country is meeting its aims. Results are presented in terms of changes in the welfare indicators, and the extent to which Mozambique is on course to achieve the Millennium Development Goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet